Investigation of the relationship between depression and nutritional status of elderly patients in home care - Karakaş, Neşe; Bentli, Recep; Fırıncı, Betül; Zabcı, Bilge (Journal of Surgery and Medicine, 2019)
Aim: Malnutrition and depression are common geriatric disorders. The aim of this study was to determine the prevalence of malnutrition and depression in the elderly, as well as assess the association between depression and malnutrition. Methods: A cross-sectional study was conducted with 86 elderly patients in the external consultation unit of a public specialty hospital in Malatya. Nutritional status was classified by the Mini Nutrition Assessment (MNA). Depression was assessed using the Geriatric Depression Scale (GDS). Functional autonomy indicators were obtained by Katz Index. Results: A total of 86 patients, 27 females and 59 males, were included in this study. Among them, 12.8% were classified as in adequate nutritional status, 50.0% were classified as being at risk of malnutrition and 37.2% as malnourished. In this study, depression rate was determined as 79.1% according to the GDS. MNA scores, hand grip strength and folic acid levels of the group diagnosed with depression were statistically significantly lower (p˂0.001, P=0.03, P=0.04, respectively). Conclusion: We suggest routine screening of depression symptoms in addition to the nutritional disorders for the early diagnosis and treatment of malnutrition and depression, however, further studies including more patients are needed.